Pendampingan Metode An-Nahdiliyah dalam Meningkatkan Pengetahuan Baca Al-Quran Anak-anak di TPQ Roudlotul Abidin Desa Dadapan - Cahyono, Laras Tunggal; Rohman, M. Fathor; Finurika, Isna; Zaini, Ahmad Afan (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The An-Nahdiyah method is one of the learning methods of reading the Qur'an that emphasizes more on the suitability and regularity of reading using murotal beats or walkways. Al-Qur'an Education Park is a non-formal religious educational institution that teaches reading and writing the letters of the Qur'an to children from an early age, and instills akhlakul karimah contained in the Qur'an. This research is motivated by the many learning models or methods used at TPQ to make it easier for students to learn to read the Qur'an properly and correctly, so that each method has its own advantages and weaknesses in learning to read the Qur'an. One of the methods used in TPQ is the An-Nahdiyah method, the method is considered practical and lightweight for beginner learning. The problem that occurs here is that there are still students who cannot adjust the reading to the song used. The purpose of this study in general is to improve the ability of students in the An-Nahdiyah method in improving the properly and correctly